Experiences of psychological and psychotherapeutic support for LGBT youth who have survived a suicide process - Tomicic, Alemka; Martínez, Claudio; Immel, Nina (Revista Interamericana de Psicología/Interamerican Journal of Psychology, 2021)
The high prevalence of mental health problems in LGBT people has been explained from the minority stress model. Homolesbobitransphobia and the internalization of stigma are stress processes that impact mental health. The internalization and hypervigilance of the stigma and the concealment of sexual diverse identity can be barriers to the provision of appropriated mental health care. In order to identify aspects that constitute barriers and facilitators for mental health care, 30 interviews from a previous study with LGBT adolescents and youth who had survived suicide were re-analyzed. Focused coding of the Grounded Theory was used, developing three core categories: Hypervigilance in psychological help, The need for help for internalized stigma, and The place of sexual orientation and gender identity in psychological help. From the analysis emerged global concept called "So Close yet So Far", synthesizing the barriers to provide psychological and psychotherapeutic help that is sensitive to the needs of LGBT adolescents and youth.